17 Safety and patient-reported outcomes in patients receiving niraparib in the PRIMA/ENGOT-OV26/GOG-3012 trial. (13th November 2020) - Freyer, G; Pothuri, B; Han, S; Chase, D; Monk, B; Heitz, F; Burger, R; Gaba, L; Van Le, L; Guerra, E; Bender, D; Korach, J; et al.
Abstract : Introduction: Niraparib is a poly(ADP-ribose) polymerase inhibitor approved for treatment in heavily pretreated patients and maintenance of patients with newly diagnosed or recurrent ovarian cancer following a response to platinum-based chemotherapy. Here we report safety and patient-reported outcomes (PROs) in the overall population and subgroups from PRIMA/ENGOT-OV26/GOG-3012 (NCT02655016 ). Methods: This double-blind, placebo-controlled, phase 3 study randomized 733 patients. Patients received a 300-mg QD fixed starting dose (FSD) of niraparib or placebo for 36 months or until progression/toxicity. A protocol amendment introduced an individualized starting dose (ISD): 200 mg in patients with body weight <77 kg or platelets <150, 000/µL, or 300 mg in all others. The primary endpoint was PFS; safety and PROs were secondary endpoints. Safety data were collected at each visit and graded using CTCAE v4.03. PRO instruments (FOSI, EQ-5D-5L, EORTC-QLQ-C30, and EORTC-QLQ-OV28) were collected Q8W for 56 weeks, then Q12W while a patient received treatment. Results: In the overall population, the most common grade ≥3 treatment-emergent adverse events (TEAEs) were hematologic (table 1 ). In patients receiving ISD, these TEAEs decreased. No treatment-related deaths occurred. PRO analysis showed no difference in niraparib-treated patients versus placebo in the overall population or in the homologous recombination deficient, homologous recombination proficient, FSD, and ISD subgroups. Conclusions: ISD incorporation improved the safety profile of niraparib without compromising efficacy. Niraparib was well tolerated, with similar PRO scores across the treatment period. Hematologic toxicities were manageable through implementation of dose interruptions and reductions. Funding: GlaxoSmithKline NCT: NCT02655016